DEVELOPMENT & STABILITY OF COASTAL SAND SPIT - Azlina Binti Aminulla, Azlina (Universiti Teknologi Petronas, 2010)
This research is focusing on the cause of the development of sand spit and the tidal prism. Comparison between sand spit occurrences are made to see the common features between the sand spit and to determine what are the effects towards its development.